Confirmation of the Applicability of Skeletochronology and Estimating the Age Structure of Kaloula borealis (Microhylidae: Anura) at Lake Sihwa, South Korea - Md Mizanur Rahman; Yu-Young Lee; Seung-Min Park; Choong-Ho Ham; Ha-Cheol Sung (Biology, 2022)
Despite having some limitations, the use of skeletochronology—age determination by counting lines of arrested growth (LAGs)—in amphibians is increasing. The main limitation of using skeletochronology is identifying the innermost visible line (IVL) and counting the exact number of LAGs. Thus, we tested its applicability to Kaloula borealis, a class II endangered amphibian in South Korea. We reared juveniles in the lab to investigate the process of bone formation. This confirmed the development of one LAG each year. Hence, our study validates skeletochronology for the age determination of this species and recommends it for others that show similar growth patterns. Furthermore, the comparison of threshold diameters with the IVL of wild individuals confirmed no LAG1 resorption. The average age of males and females in this population was 2.75 ± 1.05 and 3.64 ± 3 years, respectively. We estimated sexual maturity at 2 years with rapid growth up to that stage in both sexes. We found a female-dominated sexual size dimorphism. This study offers accurate information on the life history traits and age structure of K. borealis that may help to evaluate population dynamics in other areas, identify vulnerable life stages and sites, assess the causes of population decline, and set conservation priorities.